Reuse of Industrial heritage in Florianópolis/SC (PerCursos, 2025)
This paper addresses concerns regarding contemporary interventions on heritage assets, analyzing two significant examples of built industrial heritage important to the urban landscape and memory of Florianópolis/SC. With the generalization of industrial substitution and relocation processes, the importance of preserving these landscapes is highlighted, especially considering the rapid substitution processes in Brazilian cities, driven by the fragility of urban legislation that favors the accelerated dynamics of real estate capital. The case study focuses on two projects in the central area of Florianópolis: Top Vision (former Hoepcke Embroidery and Lace Factory) and Armazém Rita Maria (former Hoepcke Navigation Warehouses and Rita Maria Point Factory). Analysis of municipal laws revealed that approval processes are quite confusing and frequently disregard the technical opinions of regulatory and/or responsible bodies. This result provokes discussions about the processes of renovation, whether of the building or its use, of the heritage to attract contemporary consumption practices, linked to tourism and the interests of the supposed holders of power. These groups spatialize their territorial domination through real estate speculation and unrestrained verticalization, disrespecting heritage assets, collective memory, and the local landscape. It is concluded that these spaces are becoming major reproducers of the hegemonic logic of capital reproduction, present in any location destined for consumption.
Keywords: industrial heritage; urban rehabilitation; social memory